Comparative cytotoxicity of chelidonine and homochelidonine, the dimethoxy analogues isolated from Chelidonium majus L. (Papaveraceae), against human leukemic and lung carcinoma cells - Havelek, Radim; Seifrtova, Martina; Královec, Karel; Kročová, Eliška; Tejkalová, Veronika; Novotny, Ivan; Cahlikova, Lucie; Safratova, Marcela; Opletal, Lubomir; Bílková, Zuzana; Vavrova, Jirina; Rezacova, Martina (Elsevier GmbH, 2016)
In this study the effects of naturally occurring homochelidonine in comparison to chelidonine on cell cycle progression and cell death in leukemic T-cells with different p53 status are described. We found that homochelidonine and chelidonine displayed significant cytotoxicity in examined blood cancer cells with the exception of HEL 92.1.7 and U-937 exposed to homochelidonine. Unexpectedly, homochelidonine and chelidonine-induced cytotoxicity was more pronounced in Jurkat cells contrary to MOLT-4 cells. Homochelidonine showed an antiproliferative effect on A549 cells but it was less effective compared to chelidonine. Biphasic dose-depended G1 and G2/M cell cycle arrest along with the population of sub-G1 was found after treatment with homochelidonine in MOLT-4 cells. In variance thereto, an increase in G2/M cells was detected after treatment with homochelidonine in Jurkat cells. Treatment with chelidonine induced cell cycle arrest in the G2/M cell cycle in both MOLT-4 and Jurkat cells. MOLT-4 and Jurkat cells treated with homochelidonine and chelidonine showed features of apoptosis such as phosphatidylserine exposure, a loss of mitochondrial membrane potential and an increase in the caspases -3/7, -8 and -9. Western blots indicate that homochelidonine and chelidonine exposure activates Chk1 and Chk2. Studies conducted with fluorescence microscopy demonstrated that chelidonine and homochelidonine inhibit tubulin polymerization in A549 cells. Collectively, the data indicate that chelidonine and homochelidonine are potent inducers of cell death in cancer cell lines, highlighting their potential relevance in leukemic cells.
Porovnání cytotoxicity chelidoninu a homochelidoninu, dimethoxy analoga izolovaného z Chelidonium majus L. (Papaveraceae), vůči lidským leukemickým a plicním nádorovým buňkám
Keywords: Homochelidonine; Apoptosis; Biphasic cell cycle arrest; Mitotic block; Homochelidonin; Apoptóza; Bifázická zástava buněčného cyklu; Mitotický blok